The Application of Multi-Contract In Griya Hijrah Products Based On DSN-MUI Fatwa No. 31/DSN-MUI/VI/2002 AT BSI KCP Diponegoro 2 Surabaya - Arista, Anis; Maknuun, Lu’lu’il (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
This study ains to determine the implementation of multi-contract and the relevance of Fatwa DSN-MUI No.31/DSN-MUI/VI/2002 on the implementation of the multi-contract on griya hijrah products at BSI KCP Diponegoro 2 Surabaya. The type of research used is field research with a qualitative approach. The results of this study are: 1) The implementation of the qardh wal murabahah contract begins with the customer applying for financing to BSI KCP Diponegoro 2 Surabaya. Then BSI provides qardh funds in accordance with the remaining obligations and the customer pays off the debt at the previous bank. After paying off, the customer sells the asset to BSI and BSI sells it back in murabahah to the customer along with a margin and the customer can install the financing. 2) The implementation of the qardh wal murabahah contract on the griya hijrah product at BSI KCP Diponegoro 2 is relevant to Fatwa DSN-MUI No.31/DSN- MUI/VI/2002 using the first alternative.